The Effect of Flexi-Benefit Programs and Employee Financial Education on the Financial Satisfaction and Productivity of Millennial Employees in West Java - Azwar, Edy; Novitasari, Salwa Aulia; Arini, Rani Eka (West Science Interdisciplinary Studies, 2025)
This study investigates the effects of flexi-benefit programs and employee financial education on financial satisfaction and employee productivity among millennial employees in West Java. Using a quantitative explanatory design, data were collected from 115 respondents through a structured questionnaire employing a five-point Likert scale. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to examine both direct and mediating relationships among the variables. The findings reveal that flexi-benefit programs and financial education each have a significant positive effect on financial satisfaction and productivity. Moreover, financial satisfaction serves as a key mediating variable that strengthens the relationship between organizational financial initiatives and employee productivity. The results affirm the integration of Self-Determination Theory, Human Capital Theory, and Conservation of Resources Theory, indicating that financial autonomy, knowledge, and security collectively enhance employee performance. This research contributes to the literature on employee financial well-being and provides practical implications for organizations aiming to improve millennial workforce engagement and productivity through flexible compensation and financial literacy programs.